Antinociceptive and anti-inflammatory effects of Caryocar coriaceum Wittm fruit pulp fixed ethyl acetate extract on zymosan-induced arthritis in rats. (4th November 2015) - de Oliveira, Francisco Fábio Bezerra; de Araújo, Joana Cláudia Bezerra; Pereira, Anamaria Falcão; Brito, Gerly Anne Castro; Gondim, Delane Viana; Ribeiro, Ronaldo de Albuquerque; de Menezes, Irwin Rose Alencar; Vale, Mariana Lima
Abstract: The ethyl acetate extract from the fruit pulp of Caryocar coriaceum Wittm (Caryocaraceae), popularly known as pequi, has wide applications in popular medicine. Preclinical tests have demonstrated the therapeutic properties of the oil. We investigated the antinociceptive and anti-inflammatory effects of Pequi C. coriaceum Wittm ethyl acetate extract (PCCO) on zymosan-induced arthritis in rat knee joint. The animals were pretreated with PCCO for 7 consecutive days or with a single dose. Paw elevation time (PET), leukocyte infiltration, myeloperoxidase activity (MPO) and cytokine levels were assessed 4 h after zymosan injection. Synovial tissue was harvested for immunohistochemical analysis, edema and vascular permeability. We observed a significant decrease in PET with PCCO pretreatment. PCCO showed a significant reduction of leukocyte migration and a decrease in MPO. Decreases were observed in cytokine release in the synovial fluid and TNF-α and cyclooxygenase-1 immunostaining in synovial tissue. Edema was inhibited by treatment with all doses of PCCO. The data suggest that PCCO exerts antinociceptive and anti-inflammatory effects on arthritis in rats. Graphical abstract: